Relationship of Physiographic Position to Physicochemical Characteristics of Soils of the Flooded-Savannah Agroecosystem, Colombia. (2023)
Savannah floodplains are a natural agroecosystem located in the eastern plains of Colombia, with soils considered to be of low fertility. This assumption has not been rigorously validated by direct experimental studies. The aim of the study was to analyze the soils’ physicochemical characteristics of the “banks” and “lows”, which are physiographic positions, from the floodplain savannah in Arauca, Colombia. Soil samples were collected in “low” (n = 14) and “bank” (n = 15) physiographic positions. For each soil sample, the following chemical variables were determined: pH, organic carbon (OC), total nitrogen (TN), P, K, Ca, Mg, Na, exchange acidity, cation-exchange capacity (CEC), Fe, Cu, Mn, Zn and B, and physical variable (texture). The Wilcoxon non-parametric test (Mann–Whitney) was applied for the comparison of the soil’s physicochemical variables in each physiographic position (p < 0.05). The highest values for each variable analyzed correspond to the physiographic position of “low” (p < 0.05). The pH, T.N., Na, K and B were not statistically significant (p > 0.05). The physiographic positions of “bank” and “low” of floodplain savannah presented low levels of most nutrients, with slightly higher values in the “low” physiographic position. Corrective measures must be applied to improve the nutritional values of savannah soils and, consequently, the productivity of native forages. Despite these deficiencies, the vegetation cover is given by very well-adapted native grasses, reflecting the conditions of said agroecosystem.